Collective approaches for facilitating farmer innovation - CGIAR Program on Collective Action and Property Rights (International Food Policy Research Institute, 2010)
Participatory application of planning methods such as logical framework analysis empowers local stakeholders to make decisions. Integrated pest management, which relies on coordinated action among neighboring farmers, has shown the value of integrating local and scientific knowledge. Technical tools, such as geographic information systems and computer models, can support better-informed decision-making by local stakeholders. Sustaining changes beyond the stages of initial enthusiasm requires good follow-through from planning to action and a supportive institutional environment.